2007
DOI: 10.1658/1100-9233(2007)18[827:accipr]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Afforestation causes changes in post-fire regeneration in native shrubland communities of northwestern Patagonia, Argentina

Abstract: Question:What are the effects of fire in native shrubland communities and in pine plantations established in these shrublands? Location: Northern Patagonia, Argentina. Methods: We surveyed four sites in Chall-Huaco valley, located in northwest Patagonia. Each site was a vegetation mosaic composed of an unburned Pinus ponderosa plantation, a plantation burned in 1996, and an unburned matorral and a matorral burned by the same fire. We recorded the cover of all vascular plant species. We also analysed species ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
(17 reference statements)
2
7
0
2
Order By: Relevance
“…The point not in a circle was uninvaded and burned and still had no P. contorta when sampled after fire. More severe soil heating with increasing levels of invasion may explain the different post-fire trajectories seen in sites dominated by pines compared to native-dominated sites in our study and others (Holmes et al 2000, Nuñez and Raffaele 2007, Zalba et al 2008). If seedbanks and resprouting plants are destroyed by fire, then native regeneration is more dependent on distance to nearest seed source.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…The point not in a circle was uninvaded and burned and still had no P. contorta when sampled after fire. More severe soil heating with increasing levels of invasion may explain the different post-fire trajectories seen in sites dominated by pines compared to native-dominated sites in our study and others (Holmes et al 2000, Nuñez and Raffaele 2007, Zalba et al 2008). If seedbanks and resprouting plants are destroyed by fire, then native regeneration is more dependent on distance to nearest seed source.…”
Section: Discussionsupporting
confidence: 43%
“…In South Africa, soil properties under burned pine canopies and native fynbos suggested that fire severity was higher in pine plantations than in fynbos (Scott and Van Wyk ). In Patagonia, post‐fire Pinus ponderosa plantations created novel conditions that prevented regrowth of native matorral (shrubland), despite the fact that matorral is well adapted to surface fire (Nuñez and Raffaele ). Whether the post‐fire vegetation trajectories differed due to pre‐fire species composition or changes in fire severity in this study is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Fire‐adapted invasive pines exert positive feedbacks on fire, and fire in turn can stimulate pine regeneration (Baker, ; Richardson & Cowling, ). Although some communities are resilient to invasion of pines followed by fire (Nuñez & Raffaele, ), other communities can be replaced with fire‐adapted communities as a consequence of the invasion of fire‐adapted pines. Taylor et al.…”
Section: Why Have Pines Become the Dominant Conifer Taxon In Many Envmentioning
confidence: 99%
“…Previous studies of post‐fire succession have primarily concentrated on the direct impacts of fire on forest recovery and linked those impacts to factors such as disturbance history, the regional species pool and species life histories (Girard, De Grandpré, & Ruel, ; Schoennagel, Veblen, & Romme, ). However, the specific role of biotic and abiotic factors in post‐fire regeneration can differ substantially among fires (Ackerly, ; Camac, Williams, Wahren, Morris, & Morgan, ; Nuñez & Raffaele, ), depending on the context provided by the characteristics of the local environment. Under certain unique geographical conditions, succession cannot be completely described by a general pattern of community development, but rather is the result of a variety of dynamic site‐specific factors that change the trajectory from the typical chronosequence (Conway & Johnstone, ; Yuan et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of post-fire succession have primarily concentrated on the direct impacts of fire on forest recovery and linked those impacts to factors such as disturbance history, the regional species pool and species life histories (Girard, De Grandpré, & Ruel, 2014;Schoennagel, Veblen, & Romme, 2004). However, the specific role of biotic and abiotic factors in post-fire regeneration can differ substantially among fires (Ackerly, 2004;Camac, Williams, Wahren, Morris, & Morgan, 2013;Nuñez & Raffaele, 2007), depending on the context provided by the characteristics of the local environment.…”
Section: Introductionmentioning
confidence: 99%